Arena-Anchored Urban Development Projects and the Visitor Economy - Barry, Taryn; Mason, Daniel S.; Trzonkowski, Robert (Frontiers in Sports and Active Living, 2022)
Cities of all sizes are actively engaged in developing various urban infrastructure projects. A common strategy used in larger North American cities is employing arena-anchored urban development projects, where a professional sports team is used as an anchor tenant of a sports facility to generate development in the city. One means of relocating economic activity is to increase visitation to the desired redevelopment area. In this paper we used the visitor economy as a lens to explore how arena-anchored projects and the professional sports teams that play there fit into a local city's tourism economy. To conduct this study, a multi case study design was used to draw data from two cities: Columbus, Ohio, and Detroit, Michigan. Interviews were goal directed and conducted in person with leaders in Columbus (n = 9) and Detroit (n = 10), and inductive and deductive approaches to coding were undertaken in the form of content analysis. The results indicate that growing the visitor economy through arena anchored urban development relies on planned placemaking via the strategic approach of bundling diverse amenities together. These findings provide valuable feedback to those cities considering arena development projects, and how the arenas may be combined with other civic amenities to undergird the local visitor economy.